Literature Review: Implications of Inclusive Education in Indonesia According to the Thoughts of Socrates, Aristotle, John Dewey and J.J. Rousseau - Ana Rafikayati; Acep Ovel Novari Beny; Asri Wijiastuti (Didaktika: Jurnal Kependidikan, 2025)
This article was written with the aim of presenting a literature review to understand the thoughts of philosophers related to the implications of inclusive education, equality, participation, and diversity in the time period between 2014-2024. This research uses a literature study method with the Systematic Literature Review (SLR) method. The researcher collected articles from journals relevant to the topic of the thoughts of philosophers related to the implications of inclusive education, equality, participation, and diversity. The literature search was conducted by accessing the online database from Google Scholar with a publication spanning the last 10 years, namely 2014-2024. The results obtained from the search revealed 20 articles relevant to the research topic. The results indicate that inclusive education in Indonesia requires a strong philosophical foundation to realize equality, participation, and respect for diversity. The thoughts of philosophers such as Socrates, Aristotle, Rousseau, Dewey, and Freire demonstrate the relevance of building a just and democratic educational paradigm. However, its implementation still faces challenges, requiring synergy between philosophical theory, policy, and learning practice to achieve the goals of inclusive education.